Early selection for grain yield in Arabica coffee using morphological traits evaluation - Teixeira, Alexsandro Lara; Gonçalves, Flávia Maria Avelar; Rezende, Juliana Costa de; Carvalho, Samuel Pereira de; Pereira, Antônio Alves; Moraes, Bráulio Fabiano Xavier de; Teixeira, Luíz Gustavo Vieira (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the viability of early selection in Arabica coffee using the correlation between morphological traits and grain yield. Two hundred and sixty‑nine accessions of Coffea arabica, among cultivars, hybrids, and wild genotypes, from Epamig’s coffee germplasm bank, Patrocínio, MG, Brazil, were evaluated. A randomized complete block design was used, with two replicates, at a spacing of 3.5x0.8 m, with ten plants per plot. Morphological traits were evaluated in 2006, 12 months after planting, when plants were still at the juvenile phase. Grain yield data are from the 2008/2009 and 2009/2010 crop seasons. The length of the first plagiotropic stem, at 12 months of age, was highly correlated and showed a high direct effect in a favorable direction toward grain yield, being the main morphological trait responsible for variations in grain yield. The vegetative vigor at 12 months of age was the most important secondary variable in explaining the variations in grain yield. These traits can be used effectively in the early selection for grain yield in Arabica coffee.